2014
DOI: 10.1182/blood-2013-05-500272
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Asxl1 leads to myelodysplastic syndrome–like disease in mice

Abstract: Key Points Deletion/haploinsufficiency of Asxl1 causes MDS-like disease in mice. Asxl1 loss reduces the HSC pool and decreases HSC hematopoietic repopulating capacity in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
188
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(193 citation statements)
references
References 37 publications
5
188
0
Order By: Relevance
“…) resulted in developmental abnormalities and onset of MDS-like disease, including dysplastic neutrophils and multiple lineage cytopenia [91]. Mice with hematopoietic-specific conditional deletion of Asxl1 also developed MDS-like disease with multilineage cytopenias and dysplasia in the context of increased numbers of HSPCs [92], underscoring the importance of ASXL1 in MDS pathogenesis.…”
Section: Asxl1mentioning
confidence: 99%
“…) resulted in developmental abnormalities and onset of MDS-like disease, including dysplastic neutrophils and multiple lineage cytopenia [91]. Mice with hematopoietic-specific conditional deletion of Asxl1 also developed MDS-like disease with multilineage cytopenias and dysplasia in the context of increased numbers of HSPCs [92], underscoring the importance of ASXL1 in MDS pathogenesis.…”
Section: Asxl1mentioning
confidence: 99%
“…An animal study has shown that Asxl1 deletion or haploinsuffiency constitutes a sufficient condition for the development of myeloid neoplasia reminiscent of MDS and MDS/myeloproliferative neoplasms. 4 In another study the transplantation of bone marrow cells expressing oncogeneic…”
Section: Introductionmentioning
confidence: 99%
“…ASXL1 mutations in patients with myelodysplastic syndrome (MDS) and chronic myelomonocytic leukemia (CMML) usually correlate with acute transformation and worse prognosis [23][24][25]. Recently, mouse genetic studies confirmed that loss of function of Asxl1 leads to MDS-like defects [26][27][28], and that loss of Asxl1 in combination with activated N-Ras or loss of Tet2 increases the severity of the hematological malignancy [27,28]. Mechanistically, Abdel-Wahab et al [29] showed that ASXL1, as a tumor suppressor, prevents the expression of oncogenes like HOXA9 by association with PRC2.…”
Section: Introductionmentioning
confidence: 99%